Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

If f(x) = 3x-1 and g(x)= x+2 find (f-g) (x)

Sagot :

Answer:

2x-3

Step-by-step explanation:

f(x) = 3x-1

g(x)= x+2

(f-g) (x) = 3x-1 - (x+2)

Distribute the minus sign

             = 3x-1 -x-2

 Combine like terms

               = 3x-x -1-2

                =2x -3